Perbandingan Residual Income Model Dan Free Cas Flow To Equity Model Dalam Penilaian Saham - Anugrah Ugga Praceka; Rahmat Setiawan (STIE AMKOP, 2023)
This study aims to compare the accuracy of the Residual Income Model (RIM) and the Free Cash Flow to Equity Model (FCFEM) in assessing the stock prices of companies listed on the Indonesia Stock Exchange. The sample of this research is stocks of non-banking companies included in the IDX HIGH DIVIDEND 20 index. The approach used in this study is a quantitative approach using the Mann-Whitney U Test and compare means of two groups. By comparing the Absolute Percentage Error generated from RIM and FCFEM, the results of this study indicate that the RIM method is more accurate than the FCFE method in assessing stock prices. Keywords: Stock Valuation; RIM, FCFEM, Absolute Percentage Error